2020
DOI: 10.1007/s11368-020-02772-3
|View full text |Cite
|
Sign up to set email alerts
|

Do earthworms (D. veneta) influence plant-available water in technogenic soil-like substrate from bricks and compost?

Abstract: Purpose Topsoil and peat are often taken from intact rural ecosystems to supply the urban demand for fertile soils and soil-like substrates. One way of reducing this exploitation is to recycle suitable urban wastes to produce Technosols and technogenic soil-like substrates. In this study, we investigate the role earthworms can play in impacting the hydraulic properties of such a soil-like substrate. Materials and methods In a 4-month microcosm experiment, the influence of the earthworm species D. veneta on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In order to optimise the properties of Technosols, the presence of worms and plants is required (Deeb et al, 2017). It has been shown that the earthworm species Dendrobaena veneta was able to improve properties such as plant available water content in Technosols (Ulrich et al, 2021). Earthworm activity can also promote SOC stabilisation (Le Mer et al, 2020).…”
Section: Organic Waste Recycling To Foster Soil Organic Carbon Storag...mentioning
confidence: 99%
“…In order to optimise the properties of Technosols, the presence of worms and plants is required (Deeb et al, 2017). It has been shown that the earthworm species Dendrobaena veneta was able to improve properties such as plant available water content in Technosols (Ulrich et al, 2021). Earthworm activity can also promote SOC stabilisation (Le Mer et al, 2020).…”
Section: Organic Waste Recycling To Foster Soil Organic Carbon Storag...mentioning
confidence: 99%
“…Tams et al (2022) showed in a life cycle analysis, that the use of recycled brick particles instead of expanded clay reduces the CO2 footprint of the substrate layer by 50 % in an extensive green roof. The composition of waste materials and the processing (Ulrich et al, 2021) are the most important design levers to manipulate the properties according to their targeted application (Rokia et al, 2014;Fields et al, 2018;Willaredt and Nehls, 2021). Most UGI addresses the re-establishment of soil function related to the regulation of the water cycle (Grabowski et al, 2022).…”
Section: Introductionmentioning
confidence: 99%